Promoting Employee Green Behavior Through the Person-Organization Fit: The Moderating Effect of Psychological Distance - Mi, Lingyun; Sun, Yuhuan; Gan, Xiaoli; Yang, Hang; Lv, Tao; Shang, Ke; Qiao, Yaning; Jiang, Zhiping (Frontiers in Psychology, 2020)
The importance of employee green behavior (EGB) to an enterprise’s green development goal has been increasingly emphasized. However, promoting employee green behavior through the interaction between individuals and organizations has not been a central concern. Therefore, from the perspective of the person-organization fit, this study considers the psychological distance between employees and the organization as the moderating variable to explore the mechanisms of values fit, needs-supplies fit, and demands-abilities fit on green behaviors within and outside the responsibilities of employees. After collecting the results of questionnaires from 412 employees, our hypotheses were tested using the Structural Equation Model (SEM). The results show that (1) person-organization fit can effectively promote EGB in the workplace. However, different types of person-organization fit have different influencing paths and effect-strengths on employees’ task-related green behavior and proactive green behavior. (2) Values fit has the greatest incentive effect on EGB, followed by demands-abilities fit, while needs-supplies fit promotes only eco-helping behavior. (3) Psychological distance has a significant moderating effect on the relationship between the person-organization fit and EGB. Specifically, the effect of person-organization fit on EGB is enhanced in the case of close emotional distance, while the effect is weakened in the case of close expectation distance. Finally, this study provides suggestions for enterprise managers on ways to motivate EGB through the selection and allocation of human resources.